1997
DOI: 10.1021/jm970312l
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Cardiotonic Activity, and Structure−Activity Relationships of 17β-Guanylhydrazone Derivatives of 5β-Androstane-3β,14β-diol Acting on the Na+,K+-ATPase Receptor

Abstract: A series of digitalis-like compounds, with the lactone ring shifted from the original position through a spacer or replaced by a series of guanylhydrazone substituent-bearing chains, was synthesized and evaluated for inhibition of Na+,K(+)-ATPase and for inotropic activity. The highest Na+,K(+)-ATPase inhibition (IC50) and inotropic activity (EC50) were reached with the vinylogous guanylhydrazone 5 where a cardenolide-like polarized alpha,beta-unsaturated system and a basic guanidino group were both present at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 15 publications
2
21
0
Order By: Relevance
“…From these new findings and the data reported in the previous papers, [3][4][5] we reasoned that this extraordinary activity could be ascribed to an interaction of the protonated amine substituent with a negatively charged site in the receptor. With the aim of finding if this putative "anionic site" really existed, we started a The EZ mixture is indicated where the amount of Z oxime is more than 10%.…”
Section: Introductionsupporting
confidence: 58%
“…From these new findings and the data reported in the previous papers, [3][4][5] we reasoned that this extraordinary activity could be ascribed to an interaction of the protonated amine substituent with a negatively charged site in the receptor. With the aim of finding if this putative "anionic site" really existed, we started a The EZ mixture is indicated where the amount of Z oxime is more than 10%.…”
Section: Introductionsupporting
confidence: 58%
“…Colchicine is used for treatment of gouty arthritis and Mediterranean fever; its toxic effect is related to tubuline depolymerization. Digoxin is a cardiotonic glycoside used to control ventricular rate in atrial fibrillation with a small margin between toxic and therapeutic doses; it acts on the Na+/K+ ATPase receptor [44]. Vincristine and vinblastine are anti-tumor microtubule modulators.…”
Section: Cell Viability and Animal Toxicitymentioning
confidence: 99%
“…13 In naturally occurring digitalis glycosides the unsaturated g-and d-lactones present in 17b-position of the steroidal skeleton are associated with high affinity for the Na þ /K þ -ATPase receptor. 15,16 Recently, it was confirmed that basicity, i.e. a strong ionic interaction between one of carboxylate residues present in the a-subunit of the Na þ /K þ -ATPase and the cationic form of some digitalis like derivatives is relevant for interference with enzyme activity.…”
Section: Introductionmentioning
confidence: 99%